How to Make Friends and Influence People: Elementary Education, French “Influence,” and the Balkans, 1815–1830s - Tipei, Alex R. (Modern Intellectual History, 2018)
This article challenges the notion of French “influence.” It traces a network of like-minded reformers in France and the Balkans that came together in the early nineteenth century to further popular education. Examining interactions between actors in a cultural, scientific, and political center (France) and their allies on the periphery (in present-day Greece and Romania), the article reassesses these relationships, revealing the extent to which French individuals and organizations depended on such partnerships. Conceiving of joint Franco-Balkan reform agendas as programs of development, it offers a model and a vocabulary for the study of French soft power in post-Napoleonic Europe.

Audience Matters: ‘Civilization-Speak’, Educational Discourses, and Balkan Nationalism, 1800–1840 - Tipei, Alex R. (European History Quarterly, 2018)
This article tracks how political and intellectual leaders from south-eastern Europe used the concept of civilization, or a particular type of ‘civilization-speak’, from the end of the eighteenth century through the mid-nineteenth century. It compares and contrasts how they employed civilization-speak in different linguistic milieus – French, Modern Greek, and Romanian – and how they deployed it to further changing political aims during a period of political upheaval in the Balkans. It traces how civilization-speak served initially as a tool for extracting support from west European, especially French, patrons, and was later refashioned into a rhetorical instrument of nationalism. This study places the intellectual and political history of south-eastern Europe during the era in a pan-European context and adds nuance to discussions about the development of nationalism in the region.

Civilization and the xenoi (comment) - Tipei, Alex (The Workshop, 2015)

Why All Humanists Should Go to Prison - Tipei, Alex R. (The Chronicle of Higher Education, 2016)
Academics could learn a lot from volunteering in a penal institution — about teaching, technology, and the value of a liberal-arts education.
Section: The Review